The Citation Economy as a Site of Extraction for Surveillance Publishing - Colbert-Lewis, Danielle; maminta, lawrence; McElroy, Kelly; Slaght, Graeme; Swartz, Mark (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2024)
A few companies with dominance over academic publishing have been able to capture and use surplus value created through the publishing lifecycle. This extraction—of academic labour, of data, of information—is reinvested into their proprietary data analytics products. This is both literally, as the data collected by the publishing side can be incorporated into data analytics algorithms, and financially, as the profit margins of these academic publishing arms are astonishingly high. Crucially, these profits have been used to expand these companies’ portfolios of extractive data services across industries as academic publishers transition from information vendors to technology-driven data brokers. By providing their labour directly (as editors, reviewers, etc.) or indirectly (as authors) to these companies, scholars are complicit in data collection and analysis used for everything from advertising to law enforcement. This data is sold back to universities who use it to evaluate and surveil the publishing practices of their employees, using proprietary metrics and methods that do not align with principles of academic freedom.This paper provides an overview of this landscape, concluding with implications and recommendations for the scholars and librarians ensnared in it. It also includes a mini-zine we plan to distribute to help contextualize academics’ roles in the citation economy and the ethical implications for their work.